Impacts of Pond Change on the Regional Sustainability of Water Resources in Taoyuan, Taiwan - Yuei-An Liou; Tai-Sheng Wang; Hai-Po Chan (Advances in Meteorology)
Taoyuan tableland faces the increasing water demand associated with the expansion of industrialization and urbanization. The county currently relies on the Shihmen Reservoir as the single water supply system. It will be of great concern in the shortage of water resources. This study aims to explore the impact of changes in farm ponds on the regional agricultural environment in Taoyuan County with multiyear (1993, 2003, and 2010) SPOT satellite imagery. Results show that farm ponds have decreased by 10.55 million m2 from 1993 to 2010, and the existing farm ponds were 18.80 million m2 in 2010, equivalent to the irrigation water of 21.10~31.65 million m3 (tons) and 37.61~56.41 million m3 (tons), respectively. The existing farm ponds are able to provide the water supply for 1.88~2.82 thousand hectares of agricultural land, accounting for 6.70%~10.50% of total agricultural area of Taoyuan County. Corresponding to the government’s promotion policy (2012) on activating fallow land, if we redeploy the existing farm ponds for activating fallow fields, it will lessen the water supply burden of Shimen Reservoir. Thus, farm ponds remain the significant water facilities. For the sustainable agriculture, farm ponds shall be classified and cherished as a public asset for the future development.